IMPLEMENTASI KEBIJAKAN FISKAL: PEMBIAYAAN PROGRAM PEMBANGUNAN BERBASIS RUKUN TETANGGA (PBRT) DI KABUPATEN SUMBAWA BARAT - Rudi Masniadi; David Kaluge (Journal of Indonesian Applied Economics, 2011)
Fiscal policy is one form of economic policies pursued in the context of macroeco-nomic stabilization, promote growth, equity, and sustainability menjega budget. WestSumbawa regency is one of regencies in NTB province has embarked on one of fiscalpolicy implementation is in the financing of Neighborhood-Based Development pro-gram (PBRT). PBRT program is a strategy of development by putting the region atthe lowest level of development of the neighborhood (RT). This policy is the empow-erment of RT with the understanding that the RT is not the lowest governmentalstructures and nongovernmental organizations that are able to understand all the com-plaints and needs of their citizens. RT becomes a very important institution in whichis located all the pecking order and also serves as a populist economic base which isthen defined as the Regulation (Regulation No. 27 Year 2008 regarding PBRT). Thispaper reviewed the implementation of the program PBRT is related to how big thebudget from the budget for financing. Furthermore, by using Regulatory Impact Analysiswill be analyzed whether the policy PBRT program will bring net benefits to societyand increase welfare in West Sumbawa regency.Keywords: fiscal policy, financing PBRT, regulatory impact analysis